The influence of particle content on the equi-biaxial fatigue behaviour of magnetorheological elastomers. (15th February 2015) - Zhou, Yanfen; Jerrams, Stephen; Betts, Anthony; Farrell, Gerald; Chen, Lin
Highlights: Equi-biaxial fatigue behaviour of MREs with various CI content (15–35%) was studied. Complex modulus ( E ∗ ) fell with the accumulation of cycles for each material. The change of modulus was dependent on particle content and stress amplitude applied. Each material failed in a limiting value of E ∗ ranging between 1.22 MPa and 1.38 MPa. Dynamic stored energy can be used to predict the fatigue life of MREs. Abstract: The equi-biaxial fatigue behaviour of silicone based magnetorheological elastomers (MREs) with various volume fractions of carbonyl iron particles ranging between 15% and 35% was studied. Wöhler curves for each material were derived by cycling test samples to failure over a range of stress amplitudes. Changes in complex modulus ( E ∗ ) and dynamic stored energy during the fatigue process were observed. As for other elastic solids, fatigue resistance of MREs with different particle contents was shown to be dependent on the stress amplitudes applied. MREs with low particle content showed the highest fatigue life at high stress amplitudes while MREs with high particle content exhibited the highest fatigue resistance at low stress amplitudes. E ∗ fell with the accumulation of cycles for each material, but the change was dependent on the particle content and stress amplitude applied. However, each material failed in a range suggesting a limiting value of E ∗ for the material between 1.22 MPa and 1.38 MPa regardless of the particle content and the magnitude of the stress amplitude. In keeping with results from previous testing, it was shown that dynamic stored energy can be used to predict the fatigue life of MREs having a wide variation in particle content.